The first occurrence of the enigmatic archosauriform Crosbysaurus Heckert 2004 from the Chinle Formation of southern Utah - Robert J. Gay; Isabella St. Aude (PeerJ, 2015)
Originally identified as an ornithischian dinosaur, Crosbysaurus harrisae has been found in New Mexico, Arizona, and its type locality in Texas, as well as in North Carolina. The genus has been reassessed by other workers in light of reinterpretations about the postcrania of another putative Triassic ornithischian, Revueltosaurus. The understanding of Triassic dental faunas has become more complicated by the extreme convergence between pseudosuchian archosaurs and ornithischian dinosaur dental morphologies. We report here on a new specimen of Crosbysaurus (MNA V10666) from the Chinle Formation at Comb Ridge in southeastern Utah. This new specimen is assigned to Crosbysaurus sp. on the basis of the unique compound posterior denticles, labiolingual width, and curvature. While MNA V10666 does not help resolve the affinities of Crosbysaurus, it does represent the extension of the geographic range of this taxon for approximately 250 kilometers. This is the first record of the genus Crosbysaurus in Utah and as such it represents the northernmost known record of this taxon. This indicates that Crosbysaurus was not limited to the southern area of the Chinle/Dockum deposition but instead was widespread across the Late Triassic paleoriver systems of western Pangea. The reported specimen was found in close association with a typical Late Triassic Chinle fauna, including phytosaurs, metoposaurs, and dinosauromorphs.